2018
DOI: 10.1016/j.pan.2018.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Sunitinib in patients with pre-treated pancreatic neuroendocrine tumors: A real-world study

Abstract: The present real-world experience shows that sunitinib is a safe and effective treatment for panNETs, even in the clinical setting of heavily pre-treated, progressive diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 24 publications
4
9
0
2
Order By: Relevance
“…A further two recently‐published retrospective studies, one from Italy and another from China, found similar efficacy of sunitinib in well‐differentiated pNET (Table ). The majority of the pNET were G2.…”
Section: Targeted Therapymentioning
confidence: 74%
“…A further two recently‐published retrospective studies, one from Italy and another from China, found similar efficacy of sunitinib in well‐differentiated pNET (Table ). The majority of the pNET were G2.…”
Section: Targeted Therapymentioning
confidence: 74%
“…Sunitinib and everolimus have been approved for treatment of PanNETs for many years now due to the results from the performed studies. Collected data regarding the use of both targeted agents in real world setting confirm their benefit with similar PFS and even higher RR on average in the phase IV and retrospective studies [10,[65][66][67][68][69] as you may see on Table S2. Everyday practice shows that although active, sunitinib and everolimus are derive on significant toxicity and grade 3/4 side effects for patients (Table S2).…”
Section: Evidence Supporting the Use Of Targeted Therapiesmentioning
confidence: 95%
“…В 2018 г. Raymond и соавт. [6,7] подтвердили результаты 3 фазы в исследовании 4 фазы у пациентов с прогрессирующими неоперабельными НЭО ПЖ G1-2. Медиана ВБП у пациентов, получавших сунитиниб в дозе 37,5 мг в день ежедневно, составила 13,2 месяца, а частота объективных ответов -24,5%.…”
Section: Clinical Observationunclassified